Effect tuck jump and plyometric exercise to accuracy smash kedeng in terms of leg muscle strength - Latar, Idris Moh.; Hasbullah, Bahmid; Masbait, Ahmad Zaini; Nanda, Fitri Agung (Jurnal Pendidikan Jasmani Indonesia, 2024)
Smash is a component and determinant in the game of takraw. One of the most anticipated smashes performed during the takraw game is smash kedeng because in his behavior he always shows acrobatics that attracts the attention of the audience. This study aims to how the knee tuck jump and jump to box exercises to increase the accuracy of the smash kedeng sepak takraw in terms of leg muscle strength. This research using experimental research with quasi-experimental. The research population consisted of 70 physical education students at Pattimura University. The sample withdrawal was carried out using a purposive technique so that the sample used was 35 people. The data were analyzed statistically using the SPSS 23 application with two-way ANOVA.  The results obtained in the study were a significance value of p is 0.000 <0.05, which means that there is a significant influence between the training method ((knee tuck jump and jump to box) and leg muscle strength (high and low) the accuracy of the Kedeng Sepak Takraw smash has been proven. The conclusion of the research results revealed that the muscle power of the training program affected the results of accuracy or precision in the takraw game. The existence of this research is expected to be a reference for training training leg muscle strength in order to improve the accuracy of the kedeng sepak takraw smash.